Respuesta :
-2x³ + 3 = -x³ - x² + x + 1
Add x³ to both sides, and subtract 3 from both sides.
-2x³ + x³ = -x² + x + 1 - 3
Add like terms.
-x³ = -x²+ x - 2
Move all of the (X's) to both sides, by adding x² to both sides, and subtracting x form both sides.
-x³ + x² - x = -2
~Hope I helped!~
Add x³ to both sides, and subtract 3 from both sides.
-2x³ + x³ = -x² + x + 1 - 3
Add like terms.
-x³ = -x²+ x - 2
Move all of the (X's) to both sides, by adding x² to both sides, and subtracting x form both sides.
-x³ + x² - x = -2
~Hope I helped!~